Penerapan Model Pembelajaran Kooperative Learning Tipe Stad Terhadap Hasil Belajar IPS Siswa Sekolah Dasar - Marina Arjeni; Titi Falahiyah; Oman Farhurohman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The aim of this research is to analyze the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in improving elementary school studeny learning outcomes using a literature study methodology. The main focus of this research is onincreasing students understanding of sosial studies lesson the shortcomings and complexity of the STAD model,as well as problems that arise during its implementation. The STAD model encourages small groups to work together to improve understanding of the material. This research has been conducted using qualitative methods equipped with a descriptive approach, relying on data obtained from a literature review. Data sources include relevant scientific articles, books, and journals that support previous findings and are in line with the main topic of the study. The results of the analysis show that the STAD model has advantages such as encouraging social interaction, increasing group collaboraction, creating a conducive learning environment. However, there are shortcomings such as lack of teacher attention, difficulties in group work. As well as abstacles such as learning preparation and mastery of the material by teachers. In short the STAD model affectively improves learning outcomes and student participation.